A Comparative Study of Teachers’ Perception Towards Values Education Management According to Their Demographics at Bangkok Christian International School, Thailand - Cha, Daeyoung; Ye, Yan (Scholar: Human Sciences, 2018)
The primary purpose of this research was to determine teachers' perceptions towards values education management according to their demographics in Bangkok Christian International School in Thailand. The study surveyed all 45 teachers in Pre-school, Elementary school, and High school department at Bangkok Christian International School in Thailand during the academic year 2016-2017. The research used the questionnaire adopted from Ye’s (2006) study, based on the Ministerial Council on Education in Australian (2002). The research found that teachers' perception towards values education management at BCIS in Bangkok, Thailand was regarded as much practice, and there were no significant differences in the teachers’ perception towards values education management according to their demographics, including gender, nationality, educational background, and teaching experience at Bangkok Christian International School in Thailand. For the school improvement regarding values education management, administrators and teachers at the school were recommended to develop the channel of conversation and cooperation with parents, create projects to promote the fundamental values of Christian values, and improve the effective planning and management for enhancing Christian values development.